Engineering Technology Program in Malaysia: A Market Survey - Yahaya, Muhammad Sharil; Noordin, Aminurrashid; Ahmad, Suziana; Mohd Razali, Mohamad Sapiee (Elsevier, 2012)
In line with industrial development which is growing rapidly in Malaysia, engineering technology program is likely to be introduced in Malaysia education system at higher level. Towards developing the electrical engineering technology program and designing a curriculum structure in Universiti Teknikal Malaysia Melaka (UTeM), a market survey has been conducted to gather opinion from industries on the relevant subjects, duration of training required and also the career opportunity. The market research survey was conducted by the Committee of Development for Engineering Technology, UTeM in 2011. A total of 110 questionnaires were distributed to local and foreign companies throughout Malaysia. The scope of the market survey covered the common understanding of the concept of Engineering Technologist, requirements from industry perspective, the relevant focus areas as well as perceptions towards the program. As a result, the market research shows that there is a demand for degree programs in Electrical Engineering Technology.